1992
DOI: 10.1139/m92-190
|View full text |Cite
|
Sign up to set email alerts
|

Protein composition of Methanococcus thermolithotrophicus flagella

Abstract: KOSTYUKOVA, A. S., GONGADZE, G. M., OBRAZTSOVA, A. Y., LAURINAVICHUS, K. S., and FEDOROV, 0. V. 1992.Protein composition of Methanococcus thermolithotrophicus flagella. Can. J. Microbiol. 38: 1 162-1 166. Sodium dodecyl sulfate -polyacrylamide gel electrophoresis of flagella from the thermophilic methanogen Methanococcus thermolithotrophicus indicated that they were composed of three major proteins, with molecular weights of 62 000,44 000, and 26 000, whereas all previously studied flagella of mesophilic metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The long flagellin genes (flaB1 Mt and flaB2 Mt ) share high sequence identity; however, flaB2 Mt appears to encode an internal 220-amino-acid (220-aa) sequence that is unique to this flagellin. A previous study reported three major proteins of 62, 44, and 26 kDa in M. thermolithotrophicus flagellar filaments (30). Our analysis of KBr gradient-purified M. thermolithotrophicus flagellar filaments resulted in the identification of proteins with apparent molecular masses of 62, 44, 37, and 26 kDa by SDS-PAGE (data not shown), while the flagellin genes are predicted to encode proteins with molecular masses of 46.2, 34.9, 22.9, and 22.7 kDa.…”
Section: Resultsmentioning
confidence: 90%
“…The long flagellin genes (flaB1 Mt and flaB2 Mt ) share high sequence identity; however, flaB2 Mt appears to encode an internal 220-amino-acid (220-aa) sequence that is unique to this flagellin. A previous study reported three major proteins of 62, 44, and 26 kDa in M. thermolithotrophicus flagellar filaments (30). Our analysis of KBr gradient-purified M. thermolithotrophicus flagellar filaments resulted in the identification of proteins with apparent molecular masses of 62, 44, 37, and 26 kDa by SDS-PAGE (data not shown), while the flagellin genes are predicted to encode proteins with molecular masses of 46.2, 34.9, 22.9, and 22.7 kDa.…”
Section: Resultsmentioning
confidence: 90%
“…Cruden et al [20] reported that the integrity of £agella ¢laments from M. thermolithotrophicus was lost in the absence of high NaCl concentrations as well as when incubated at pH 11 for 1 h. However, Kostyukova et al [68] reported that ¢laments of M. thermolithotrophicus were still observed by electron microscopy after either of these treatments.…”
Section: Stabilitymentioning
confidence: 99%
“…The flagella of members of the Domain Archaea are not as well studied as their bacterial counterparts. Most of the studies of archaeal flagella and their component flagellins have been concentrated in the methanogens (Kalmokoff et al, 1988;Faguy et al, 1994b;Kostyukova et al, 1992) and extreme halophiles (Alam and Oesterhelt 1984;Gerl and Sumper, 1988;Fedorov et al, 1994). Nonetheless, many interesting features have been reported that seem to indicate that archaeal flagella are distinct from bacterial flagella in both their composition and probably also their assembly .…”
Section: Introductionmentioning
confidence: 99%